Mendorong Literasi Keuangan Digital di Desa Ponokawan, Kecamatan Krian, Kabupaten Sidoarjo - Hutabarat , Ruth Eviana; Prabowo, Prayudi Setiawan; Aji, Tony Seno; Fisabilillah, Ladi Wajuba Perdini; Arisetyawan, Kukuh; Nilasari, Aprillia; Saputra, Dimas Galih; Ratnaningsih, Ayu (Abimanyu : Jornal of Community Engagement, 2025)
Increasing financial literacy and the use of information technology can make a positive contribution to Micro, Small and Medium Enterprises (MSMEs) in terms of improving performance and ensuring business sustainability. Financial literacy helps MSME owners monitor their financial performance periodically, while information technology can be used to expand marketing reach and reach more consumers. Community service carried out by the S1 Economics Study Program of Surabaya State University (UNESA) in Ponokawan Village, Krian District, Sidoarjo Regency, East Java, aims to improve MSME financial literacy. This community service activity is carried out by providing training and assistance to MSMEs in Ponokawan Village. After going through this program, MSME owners in Ponokawan Village now have a better understanding of marketing using information technology through social media. They are also able to do bookkeeping more effectively, allowing them to monitor the financial performance of their business more accurately.